Organizational learning in the Philippines: how do team and individual learning contribute?. (October 2014) - Dayaram, Kandy; Fung, Lucia
<x xml:space="preserve">Abstract</x> Organizational learning is essential especially in rapidly changing environments, through seeking new knowledge and the effective use of existing knowledge, to unleash innovative potential. It is therefore, important to identify what increases employee engagement in these organizational learning activities. Research was conducted through a survey of local public sector employees in the Philippines to examine empirically the hypothesis that individual learning will increase employee involvement in organizational learning activities through their increased engagement in team learning activities. The findings confirm the mediating role of team learning between individual learning and organizational learning. This study also examines the distinct roles of internal (within team) and external team (across team) learning in this relationship and findings suggest team learning also plays a significant role in improving organizational performance. This study has the potential to inform the development of appropriate human resource management strategies to facilitate knowledge sharing and learning within and across teams at the local level, as a major intermediate step toward motivating employees to engage in organizational learning activities by applying their individual knowledge.